2018
DOI: 10.1002/da.22734
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with dimensional and categorical effects on white matter pathways

Abstract: Anhedonia was positively correlated with reduced FA and increased RD in white matter pathways that connect regions critical for value coding, representing stimulus-reward associations, and guiding value-based action selection. Thus, a cardinal symptom of MDD-anhedonia-was lawfully related to abnormalities in reward network connectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…Since it transmits cognitive, sensory and motor information across the hemispheres, and de cits in this area could affect complex motor tasks, such as freezing of gait (Fling, Dale et al 2016), and cognitive impairment (Bledsoe, Stebbins et al 2018) in PD patients. The neurodegeneration of corpus callosum in PD may re ect its role in motor, cognitive and emotion features (Dillon, Gonenc et al 2018), which is in accordance with our nding that the de cits of genu of corpus callosum had positive association trends with HDRS score.…”
Section: The Most Discriminative Wm Connections/regions: the Association Berssupporting
confidence: 91%
“…Since it transmits cognitive, sensory and motor information across the hemispheres, and de cits in this area could affect complex motor tasks, such as freezing of gait (Fling, Dale et al 2016), and cognitive impairment (Bledsoe, Stebbins et al 2018) in PD patients. The neurodegeneration of corpus callosum in PD may re ect its role in motor, cognitive and emotion features (Dillon, Gonenc et al 2018), which is in accordance with our nding that the de cits of genu of corpus callosum had positive association trends with HDRS score.…”
Section: The Most Discriminative Wm Connections/regions: the Association Berssupporting
confidence: 91%
“…23 In MDD, anhedonia (closely related to apathy) is associated with fractional anisotropy in the anterior cingulum and the internal capsule. 28 Using tractography, we could not find a positive association between AES scores and the number of tracts starting from the left superior frontal gyrus and the left rostral ACC (r = -0.17, p = 0.4) among participants with MDD, failing to reproduce our results for functional connectivity. We found increased fractional anisotropy in the posterior cerebellum, also involved in apathy in Parkinson disease.…”
Section: Discussioncontrasting
confidence: 79%
“…[25][26][27] Similarly, we expected to find apathy-related anatomic connectivity features in the ACC based on findings from recent literature. 28,29…”
Section: Introductionmentioning
confidence: 99%
“…Fractional anisotropy (FA) which measures the principal directionality of water diffusion is the commonly used parameter to assess whiter matter integrity in DTI studies. Decreased FA values were detected in the uncinate fasciculus, the superior longitudinal fasciculus, the cingulum, the corpus callosum (12), the genu and UF (13) in adult MDD, indicating abnormalities of white matter fiber integrity. In the recent studies of adolescent MDD, Cullen et al reported lower FA in the tract connecting subgenual ACC to amygdala (14), Bessette et al reported lower FA in corpus callosum, midbrain white matter tracts, and corticospinal tracts (15), while Aghajani et al reported lower FA in the body of the corpus callosum, as well as higher FA in the uncinate fasciculus (16), Taken together, these findings support the hypothesis that white matter deficits of frontal-limbic neural circuits may present in the early stage of depression.…”
Section: Introductionmentioning
confidence: 95%